Algorithmic exposure and identity work among Indonesia’s generation z creators: reframing work culture in the platform economy - Yazid, Muhammad Hikmal (Priviet Social Sciences Journal, 2026)
This article examines how Indonesia’s Generation Z creative workers negotiate autonomy, identity, and precarity within the algorithmic infrastructures of the digital platform economy. Drawing on a mixed-method study across Jakarta, Bandung, and Yogyakarta (n = 312 survey; 20 interviews), the paper develops an integrated model linking platform affordances, algorithmic exposure, and identity work to income volatility and well-being. While theories of platform labour and identity work often derive from Western individualistic contexts, this study positions the Indonesian case as a boundary condition—where collectivist norms and affective reciprocity modify the logic of algorithmic precarity. Findings reveal that creative autonomy is increasingly mediated by algorithmic visibility metrics, transforming personal branding into a form of economic labour. Autonomy and creative freedom coexist with structural insecurity, producing a paradox of entrepreneurial dependence. The article contributes theoretically by identifying three mechanisms—algorithmic exposure, self-branding labour, and communal buffering—that reconfigure the platform–labour–identity nexus in emerging economies. Policy implications include the need for portable social protection, algorithmic transparency, and regional creative infrastructure to stabilize digital livelihoods. By integrating quantitative indicators with qualitative narratives, the study advances a socio-economic understanding of how digital capitalism reshapes work, identity, and social reproduction in Southeast Asia.